Definition of aggressive periodontitis in periodontal research. A systematic review. (19th January 2018) - Ramírez, Valeria; Hach, Maria; López, Rodrigo
Abstract: Since its introduction in 1999, the term aggressive periodontitis (AgP) has been the topic of many investigations. Articles supporting the International Workshop for a Classification of Periodontal Diseases list several disease features, but do not offer operational criteria for identifying cases. Consequently, considerable variation in the understanding of AgP can be anticipated. Aim: To systematically assess the definitions of AgP reported in original periodontal research. Methods: A systematic review of original research on AgP published in English. Results: The electronic search yielded 833 abstracts. Of these, 472 publications fulfilled the inclusion criteria and were appraised. In 26.5% of the publications, no information on AgP operationalization is presented, but reference is made to another article. In 12.7% of the publications, no information is provided as to how the cases were defined. Many combinations of criteria for case definition were found. Conclusions: This study revealed significant heterogeneity in the understanding and use of the term AgP in original research and poor documentation of the identification of cases. The direction and magnitude of the influence of misclassification and selection bias are unknown, but ought to be considered by the critical reader, professionals and patients using this term.